PENGARUH BRAND TRUST DAN BRAND EXPERIENCE TERHADAP BRAND LOYALTY MELALUI EMOTIONAL BRAND ATTACHMENT PADA LA TULIPE KOSMETIK - Bidayah, Mila; Rakhmawati, Dwi Yuli (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
The increasingly fierce competition in the beauty industry forces every company to have a strategy to attract the emotions of Indonesian consumers to prefer local cosmetic products. This study aims to determine the effect of brand trust and brand experience on brand loyalty to La Tulipe cosmetics which is mediated through emotional brand attachment. This type of research uses quantitative research. All consumers of La Tulipe cosmetics are the population in this study. The sampling technique used a purposive sampling method, totaling 111 (one hundred and eleven) respondents. The criteria for respondents in this study are consumers who have purchased and used La Tulipe cosmetics more than twice, aged 17 years and over and domiciled in the city of Surabaya. Data collection uses a questionnaire. To evaluate the research data, we apply variance-based Structural Equation Modeling (SEM) techniques, especially Partial Least Square (PLS) which is calculated using the SmartPLS 4.0 application. The tests carried out include the outer model, inner model, suitability and goodness of the model. The research results show that brand trust has no effect on brand loyalty, brand experience has an effect on brand loyalty, emotional brand attachment has an effect on brand loyalty, brand trust has no effect on emotional brand attachment, brand experience has an effect on emotional brand attachment, brand trust has no effect on brand loyalty through emotional brand attachment, brand experience influences brand loyalty through emotional brand attachment.